2017
DOI: 10.1002/mrm.26992
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parameter accuracy on pharmacokinetic analysis of hyperpolarized pyruvate

Abstract: The accuracy and precision of k estimates improve substantially for peak signal-to-noise ratio above approximately 20. Accurate estimates of perfusion parameters (combinations of v , k , and the pyruvate vascular input function) and transmit calibration at high excitation angles have the greatest effect on the accuracy of kinetic analyses. Magn Reson Med 79:3239-3248, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…While Equation 1 can be used to model the longitudinal magnetization, signal detection requires that some of the longitudinal magnetization to be excited into the transverse plane. Previous analyses accounted for excitation losses by averaging over the TR interval . Excitation loss averaging can lead to errors in analysis .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While Equation 1 can be used to model the longitudinal magnetization, signal detection requires that some of the longitudinal magnetization to be excited into the transverse plane. Previous analyses accounted for excitation losses by averaging over the TR interval . Excitation loss averaging can lead to errors in analysis .…”
Section: Methodsmentioning
confidence: 99%
“…Previous analyses accounted for excitation losses by averaging over the TR interval . Excitation loss averaging can lead to errors in analysis . An alternative and more accurate approach applies Equation 1 iteratively over TR intervals defined to span between signal excitations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bahrami et al uses a two‐site exchange model that incorporates neither pyruvate nor lactate AIF for simplicity, and Hill et al and Daniels et al also adopted similar strategies . Recently, the works of Bankson et al and Sun et al summarized several modeling techniques, and found that a perfused‐voxel model works better than two compartments based on Akaike's information criterion in a preclinical setting …”
Section: Introductionmentioning
confidence: 99%
“…In the context of hyperpoliarized 13 C MRI, B 1 calibration is crucial for variable flip angle schemes 15,16,18 and quantification of metabolic activities. 22 Due to the virtually non-existent endogenous 13 C signal, 13 C B 1 calibration is typically performed on external phantoms, but this approach does not account for the variability of subject loading. Bloch-Siegert B 1 mapping has been applied to hyperpolarized 13 C imaging 23,24 and is advantageous due to its short acquisition time and efficient use of the hyperpolarization signal.…”
Section: Introductionmentioning
confidence: 99%